A nearly quantitative synthetic approach towards monocyclic polystyrenes and the solvent, concentration and molecular weight effect on cyclic yield. (28th September 2016) - Gao, Lingfeng; Oh, Joongsuk; Chang, Taihyun; Chen, Dongxue; Li, Xiaohong; Yang, Xiaoming; Tu, Yingfeng; Zhu, Xiulin; Li, Christopher Y.
Abstract: We report herein the effects of solvent, concentration, and molecular weight of α-alkynyl-ω-azido polystyrenes ( l -PS-N3 ) on the synthesis of monocyclic polystyrenes ( c -PS) by intra-chain coupling of l -PS-N3 via Cu-catalyzed azide/alkyne cycloaddition method. By using fully end-functionalized l -PS-N3 as precursors, the optimum cyclization conditions to synthesize high purity c -PS (>99% by SEC) are revealed, at concentrations around 7.9 μmol/L in DMF. The c -PS products are fully characterized by SEC, LCCC, 1 H NMR, and MALDI-TOF Mass spectrometry. The yield of c -PS decreases with increment of concentration of l -PS-N3 as predicted by Jacobson and Stockmayer's equation. Interestingly, among the three studied PS samples with different molecular weight (∼4k, 9k, 14k Da), the medium one (PS9k) provides the best c -PS yield, while in the three studied solvent (toluene, DMF, cyclohexane), DMF gives the best yied. The results reveal that the PS chain conformation in the solution, which is affected by the solvent and molecular weights, plays an important role in the intra-chain cyclization reaction. Graphical abstract: Highlights: Optimum cyclization conditions for the synthesis of high purity c -PS are revealed. The effect of molecular weight, concentration and solvent is systematically studied. The cyclization yield is greatly affected by the polymer chain conformation.